2016
DOI: 10.1039/c6tb01108j
|View full text |Cite
|
Sign up to set email alerts
|

New biocompatible hydroxy double salts and their drug delivery properties

Abstract: Two novel biocompatible hydroxy double salts (HDSs) have been synthesised, loaded with the drug naproxen, and formulated into tablets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 40 publications
2
12
0
Order By: Relevance
“…The X-ray diffraction (XRD) data in Figure 2 showed that the preparation of the biocompatible HDS was successful, and in accordance with the previous report (Kaassis et al, 2016a) c It should be noted that these systems are biphasic. The formula depicted is an overall empirical formula for the solid material isolated.…”
Section: X-ray Diffractionsupporting
confidence: 89%
See 2 more Smart Citations
“…The X-ray diffraction (XRD) data in Figure 2 showed that the preparation of the biocompatible HDS was successful, and in accordance with the previous report (Kaassis et al, 2016a) c It should be noted that these systems are biphasic. The formula depicted is an overall empirical formula for the solid material isolated.…”
Section: X-ray Diffractionsupporting
confidence: 89%
“…Synthesis was performed following the methods reported in our previous study (Kaassis et al, 2016a). Following a range of optimisation studies, we prepared HDSs with M:Zn ratios as close to 1:1 as we could obtain.…”
Section: Hds Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…There are four synthesis routes that have been commonly employed: ion exchange (replacement of an initial interlayer anion such as Cl -or NO 3 -with the drug), [19][20][21] reconstruction (calcination followed by reacting the calcined LDH with a solution of the drug), 22,23 exfoliation-reassembly (separation of the LDH into single layers, and then reassembly in a solution of the drug), 24 and coprecipitation (addition of a mixture of metal salts to an alkaline solution of the drug of interest to prepare an intercalate in a single-step). [25][26][27][28] Beyond LDHs, there exist other layered hydroxides which can anion-exchange and have been explored for drug delivery, such as the hydroxy double salts 29,30 or layered rare earth hydroxides (LRHs). LRHs with general formula [Ln(OH) 2 ]A n-1/n ·yH 2 O have been known for decades, but only infrequently studied since the 1970s.…”
Section: Introductionmentioning
confidence: 99%
“…A plethora of nanocarriers with organic and inorganic origins has been employed over the years to encapsulate or to adsorb drugs (Madni et al, ). Among the inorganic nanocarriers, significant amount of work has been performed using iron oxide nanoparticles (IONPs) (Arias et al, ; Chandra Mohanta, Saha, & Sujatha Devi, ; El‐Boubbou, ; J. F. Liu et al, ; Marcu et al, ; Vallabani & Singh, ; Vangijzegem, Stanicki, & Laurent, ), mesoporous silica nanoparticles (Bharti, Gulati, Nagaich, & Pal, ; Dayana, Isa, Ahmad, Basyaruddin, & Rahman, ; Vallet‐Regí, Colilla, Izquierdo‐Barba, & Manzano, ; P. Zhao et al, ; Y. Zhou, Quan, Wu, Zhang, & Niu, ), and double layered hydroxides(Bi, Zhang, & Dou, ; Kaassis, Wei, & Williams, ; Ladewig, Xu, & Lu, ; Rives, del Arco, & Martín, ; H. Wang, Wu, Zheng, & Cheng, ; Y. Xu et al, ; K. Zhang et al, ). Liposomes (Alavi, Karimi, & Safaei, ; Antimisiaris, ; Dimov, Kastner, Hussain, Perrie, & Szita, ; Sercombe et al, ; Zylberberg & Matosevic, ), carbon nanotubes (Bianco, Kostarelos, & Prato, ; Corma, Díaz, Arrica, Fernández, & Ortega, ; Elhissi, Ahmed, Dhanak, & Subramani, ; Z. Liu et al, ; Z. Liu, Sun, Nakayama‐Ratchford, & Dai, ; Z. Liu, Tabakman, Welsher, & Dai, ; Meng, Zhang, Lu, Fei, & Dyson, ; Ojima et al, ; W. Zhang, Zhang, & Zhang, ), dendrimers (Chauhan, ; Huang & Wu, ; Markowicz‐Piasecka & Mikiciuk‐Olasik, ; Mendes, Pan, & Torchilin, ; Pandita, Poonia, Kumar, Lather, & Madaan, ; Parajapati et al, ), micelles, solid lipid nanoparticles, polymeric nanoparticles, and nanogels are highlighted as organic carriers (Madni et al, ).…”
Section: Introductionmentioning
confidence: 99%